THE EFFECT OF CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), TOTAL ASSET TURNOVER (TAT) AND FIRMS SIZE (FS) TO RETURN ON EQUITY (ROE) IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2013 -2018. - Mahmudin Mahmudin; Elfreda Aplonia Lau; Beatrix Tandirerung (LPPM University 17 Agustus 1945 Samarinda, 2019)
This research was conducted to know and analysis the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT) and Firm Size (FS) on Return on Equity (ROE) in mining companies listed on the Indonesia Stock Exchange in 2013 -2018. The study was conducted using multiple linear regression methods.The results of research say that simultaneously Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT) and Firm Size (FS) have a significant effect on Return on Equity (ROE. The test results show that Partially Debt to Equity Ratio (DER) and Firm Size (FS) have a positive and significant effect on Return on Equity (ROE). While Total Asset Turnover (TAT) has a positive and significant effect on Return on Equity (ROE). On the other hypothesis testing, Current Ratio (CR) has no significant effect on Return on Equity (ROE).